The Influence of Transformational Leadership, Intrinsic Motivation, and Extrinsic Motivation on Employee Performance: Evidence from Bugisan Tourism Village - Deviasari, Cindy; Kurniawan, Ignatius Soni; Lysander, Mohammad Ahyar Syafwan (LifeSciFi, 2025)
Employee performance is a key factor in the effective management, yet challenges such as low motivation and poor coordination among managers persist. This study examines the influence of transformational leadership, intrinsic motivation, and extrinsic motivation on employee performance. A quantitative approach was applied, surveying all 80 village management employees using a census technique. Data were collected via a five-point Likert scale questionnaire and analyzed with Partial Least Squares (SmartPLS) to assess validity, reliability, and relationships between latent variables through bootstrapping. The results indicate that all three independent variables positively and significantly affect employee performance, with an R² of 0.978, demonstrating strong explanatory power. The findings suggest that combining transformational leadership with balanced intrinsic and extrinsic motivation is an effective strategy to enhance employee performance and ensure the sustainable management of culture-based tourism in the village.